MENUMBUHKAN SEMANGAT BELAJAR ANAK USIA DINI PADA MASA PANDEMI COVID 19 - Rayani, Dewi; Sarlita Kartiani, Baiq; Jaswandi, Lalu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The Covid 19 outbreak very significant impact on various sectors of individual life, one of which is the education sector. Where students and teachers alike do not have the readiness to do learning at this time. The government has issued a policy regarding not being allowed to hold crowds to stop the spread of covid 19. One of the programs in the education unit that is implemented to continue learning activities is to study from home. This study uses a descriptive qualitative method with the research subjects are teachers, parents and guardians of PAUD Permata Bangsa Mataram. collectiondata techniques using interviews, observation and various documentation. The results of the study show that there are several teacher strategies in fostering student learning enthusiasm during the Covid 19 pandemic, including, firstly, the teacher opens the communication tap with parents and the school by giving appreciation to parents in order to encourage parents and students who are getting bored with learning in the network, secondly conducting home visits and assessing the readiness to learn from home in terms of infrastructure, environmental situation and others. Provide fun learning tools for students when studying and make videos of student learning outcomes to foster student enthusiasm for learning.